2023
DOI: 10.2147/prbm.s441277
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Health-Promoting Lifestyle on Late-Onset Depression in Older Adults: Mediating Effect of Meaning in Life and Interleukin-6 (IL-6)

Miao Zhu,
Juan Zhao,
Xiaoli Zhu
et al.

Abstract: Purpose Late-onset depression (LOD) with poor treatment response has high incidence and mortality in the China’s aged people, this study aims to explore the correlation between health-promoting lifestyle, meaning in life, interleukin-6 (IL-6) and LOD for providing scientific basis of LOD prevention and rehabilitation. Patients and Methods A total of 496 LOD patients (study group) and healthy older adults (control group) were enrolled and investigated by using the Health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
0
0
Order By: Relevance
“…Health-promoting lifestyles (HPLs) refer to the multi-dimensional, spontaneous, and sustained daily activities undertaken with the aim of enhancing or promoting individual health and well-being ( 18 ). In clinical treatment, promoting the adoption of this adaptive health-promoting lifestyle is also considered a highly cost-effective and potentially applicable non-pharmacological intervention that may alleviate stress and depression ( 19 ). It showed that increasing high-intensity physical activity can alleviate the severity of mental health issues or reduce their occurrence among student populations ( 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…Health-promoting lifestyles (HPLs) refer to the multi-dimensional, spontaneous, and sustained daily activities undertaken with the aim of enhancing or promoting individual health and well-being ( 18 ). In clinical treatment, promoting the adoption of this adaptive health-promoting lifestyle is also considered a highly cost-effective and potentially applicable non-pharmacological intervention that may alleviate stress and depression ( 19 ). It showed that increasing high-intensity physical activity can alleviate the severity of mental health issues or reduce their occurrence among student populations ( 20 ).…”
Section: Introductionmentioning
confidence: 99%